A review on control of droplet motion based on wettability modulation: principles, design strategies, recent progress, and applications - Mizuki Tenjimbayashi; Kengo Manabe (Science and Technology of Advanced Materials)
The transport of liquid droplets plays an essential role in various applications. Modulating the wettability of the material surface is crucial in transporting droplets without external energy, adhesion loss, or intense controllability requirements. Although several studies have investigated droplet manipulation, its design principles have not been categorized considering the mechanical perspective. This review categorizes liquid droplet transport strategies based on wettability modulation into those involving (i) application of driving force to a droplet on non-sticking surfaces, (ii) formation of gradient surface chemistry/structure, and (iii) formation of anisotropic surface chemistry/structure. Accordingly, reported biological and artificial examples, cutting-edge applications, and future perspectives are summarized.